Revisiting Primary English Teachers’ Critical Reflections on Coursebook Usage - Senem Sahin (BIRCU, 2020)
AbstractThis study of 30 primary teachers of English in Germany used questionnaires to explore their critical reflections on coursebook usage in classrooms. The research questions were: What are primary school teachers’ perceptions of English language teaching materials? What materials are used by primary school English language teachers? What are their reasons for using certain materials? What characteristics define good language teaching materials for primary school English teachers? The participants mostly prefer implementing their own self-designed materials in combination with coursebooks. Given that preparing personal primary school teaching materials is quite time-consuming, the teachers’ arguments for their choice should be explored further to optimize English language teaching. Some argued that self-designed materials are more adjustable to the needs of their students and more authentic. The paper proposes some strategies for striking a balance between teaching English with and without a coursebook, such as making coursebook learning activities more interactive and raising awareness of effective coursebook selection. Different stakeholders can thus collect useful ideas for improvement, including teacher trainers, teachers, student teachers, school administrators, and publishers.